PENGUATAN LITERASI GURU MELALUI PENGEMBANGAN MODEL BLENDED LEARNING BERBANTUAN MOODLE - Enung Nurhayati (STKIP Siliwangi, 2022)
This research is motivated by the teacher's role in literacy skills. This role can be increased by developing training and strategies to improve teacher literacy. In this regard, this study aims to describe the implementation of training development and strategies for strengthening teacher literacy. First, analyze the needs and design of training development and teacher strengthening strategies, especially literary literacy, in the form of training models and materials/modules. The research method uses Research and Development (R&D). The research instrument at the preliminary stage used a questionnaire, while at the development stage it used an assessment instrument for training design and literacy strengthening strategies, and instruments to determine the impact of implementing and strengthening literacy strategies. Data was collected by means of observation, interviews, and field notes. The product was socialized and tested with a random sampling technique. The results of this applied research are product development through five processes, namely: 1) a preliminary study in the form of needs analysis. 2) Design of teacher literacy booster training in the form of training model designs using the Moodle-assisted Blended Learning model and learning materials or modules using the Problem Based Learning approach. 3) Validation by peer review and expert validation. 4) Evaluation of the development of training and strategies for strengthening teacher literacy. 5) Dissemination and implementation of products boldly (Moodle) and offline. Strengthening literacy is better than before, it can be seen from the higher posttest results, and the response is positive.